Catalase and enumeration of stressed Staphylococcus aureus cells. - Flowers, R S (1977)
The effects of catalase on the enumeration of stressed (heated, reduced water activity, or freeze-dried) Staphylococcus aureus cells on several selective media were examined. The addition of catalase greatly increased the enumeration of stressed cells. The beneficial effects of catalase were most pronounced on those media least efficient in enumeration of stressed staphylococci, showing increases in enumeration of up to 1,100-fold. The effects of catalase appear to be due to the reduced ability of stressed cells to repair and form colonies in the absence of an exogenous decomposer of H2O2. Thermally stressed cells were more sensitive to H2O2 than unstressed cells. During recovery, stressed cells overcame the requirement for catalase. These findings implicate H2O2 as a factor in the failure of certain selective media to adequately enumerate stressed cells and demonstrate that the addition of catalase to these media markedly increases their productivity.